The extent of the auditor's commitment to the rules of professional conduct and its impact on evaluating the companies' financial performance - Assistant. teacher Fahima Aslewah Haydow (مجلة الدراسات الاقتصادية والادارية, 2023)
Auditing accounts, international standards, international rules and standards, applicable rules, auditing standards, standards, ethics and independence in auditing financial accounts after auditing and examining them in financial auditing after auditing and examining them in financial audit. Through the questionnaire prepared on the audit side, a statistical analysis of the data was carried out then measures and tests were applied. The statistical analysis showed that there were significant statistically significant differences between the average answers 0f the respondents for the realization of this assumption, where the calculated f value amounted to 191.86, which is greater than the value of (p value). Which amounted to 0.4251 at a level of 5% morale. At that we reject the H0 null hypothesis which says that there are no significant statistically significant differences. The results of the statistical analysis revealed the existence of significant statistically significant differences. Therefore, we reject the H0 null hypothesis which states that there are no significant statistically significant differences between the mean Respond to this paragraph and accept the null hypothesis H1.